Anti-breakage and anti-leakage anhydrous stemming for blast furnace taphole and preparation method of anti-breakage and anti-leakage anhydrous stemming
By adopting a specific composition of water-free gun mud and an optimized preparation method, the blast furnace outlet gun mud is solved, and the iron outlet gun mud is not resistant to slag iron corrosion and leakage prevention performance is significantly improved, which is significantly improved the iron outlet operation efficiency and the safety and stability of blast furnace operation.
Patent Information
- Application Number
- CN202411810652.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-25
AI Technical Summary
The gun mud used in the existing blast furnace iron outlet has shortcomings in resisting slag iron erosion and leak prevention, which makes it difficult to open the iron mouth normally, increasing the difficulty of operation and waste of resources.
The anti-broken leakage-proof water-free cannon mud consisting of homogenized alumina, cyanite, silicon carbide, ferrosilicon nitride, Guangxi mud, brown corundum, alumina powder, alkali-free glass fiber, zircon, carbon materials and metal silicon are used, and the uniformity and density of the material are ensured through specific preparation methods, including mixing and premixing.
It significantly improves the flexural strength and toughness of the cannon mud, reduces the risk of leakage, optimizes the operation efficiency of the iron port, improves the safety and stability of blast furnace operations, and reduces the consumption of drill bits and refractory materials.
Smart Images

Figure BDA0005180460410000041 
Figure BDA0005180460410000051 
Figure BDA0005180460410000052
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metallurgy, and particularly relates to an anti-leakage anhydrous taphole mud for a blast furnace taphole and a preparation method thereof. Background Art
[0002] Taphole clay is a functional refractory material used to plug the taphole of a blast furnace. With the continuous development of blast furnace technology, blast furnaces are gradually moving towards high air volume, high oxygen enrichment, high top pressure, and high coal ratio, which puts higher requirements on the performance of anhydrous taphole clay. Modern blast furnaces require that taphole clay not only have good plasticity to facilitate construction operations, but also have excellent resistance to slag and iron erosion and anti-scouring properties. In addition, taphole clay needs to quickly form a dense mud bag in the taphole to protect the lining bricks in the taphole area, thereby maintaining the stability of the taphole. Especially for large blast furnaces, taphole clay must meet the higher requirements for the depth of the taphole (that is, the distance from the bottom of the furnace to the taphole of the slag and iron melt inside the blast furnace, usually in meters) to ensure the longevity of the blast furnace.
[0003] However, the problem of iron mouth leakage is still a common and difficult challenge in blast furnace production, which seriously threatens the normal operation of blast furnaces. When slag iron penetrates the pores, cracks or gaps of the taphole mud, it will corrode, infiltrate and enter the iron mouth channel. After mixing with the taphole mud, a large number of red spots will be produced when the iron mouth is opened, making it difficult to open the iron mouth normally. In severe cases, molten iron may overflow from the cracks in advance instead of flowing out from the front of the iron mouth, forming the so-called "iron mouth leakage", that is, the iron mouth is leaking. This phenomenon not only increases the difficulty of operation, but also forces workers in front of the furnace to resume production by burning oxygen to open the opening, which greatly increases the labor intensity and causes waste of resources.
[0004] With the advancement of ironmaking technology, blast furnaces are developing towards long life, enhanced smelting and large-scale development. As an important refractory material used in the taphole, the material and quality of taphole clay are constantly being improved and upgraded. It has gradually transformed from a simple consumable refractory material to a functional refractory material. Chinese patent CN 118005413 B has developed a high-strength anti-corrosion taphole clay and its preparation method, which significantly improves the strength and anti-corrosion performance of anhydrous taphole clay. However, due to its excessively high strength, the leak-breaking performance cannot be effectively guaranteed.
[0005] Therefore, it is of great practical significance to develop an anti-leakage anhydrous taphole mud with good plasticity, excellent performance, anti-leakage, and the ability to quickly form mud bags in a blast furnace. Summary of the invention
[0006] In view of the above-mentioned problems existing in the prior art, the technical problem to be solved by the present invention is to provide an anti-breakage and leakage-proof anhydrous taphole mud for blast furnace taphole, which has significant performance advantages; another technical problem to be solved by the present invention is to provide a preparation method of an anti-breakage and leakage-proof anhydrous taphole mud for blast furnace taphole.
[0007] In order to solve the above problems, the technical solution adopted by the present invention is as follows:
[0008] A water-free taphole mud for preventing leakage at a blast furnace taphole is made of the following components in parts by weight:
[0009] 8-16 parts of homogenized alumina with a particle size of 1-3mm, 8-16 parts of homogenized alumina with a particle size less than 1mm, 7-15 parts of kyanite with a particle size not greater than 1mm, 7-15 parts of silicon carbide with a particle size of 1-3mm, 10-20 parts of 325 mesh silicon carbide, 8-16 parts of 200 mesh silicon ferronitride, 4-8 parts of 200 mesh Guangxi mud, 8-16 parts of 200 mesh brown corundum, 2-4 parts of 325 mesh alumina powder, 0-0.5 parts of alkali-free glass fiber, 2-3 parts of zircon, 1-3 parts of 325 mesh carbon material, and 1-2 parts of metallic silicon.
[0010] Preferably, the anti-leakage anhydrous taphole mud for the blast furnace taphole is made of the following components in parts by weight: 12 parts of homogenized alumina with a particle size of 1-3 mm, 12 parts of homogenized alumina with a particle size less than 1 mm, 11 parts of kyanite with a particle size not greater than 1 mm, 11 parts of silicon carbide with a particle size of 1-3 mm, 15 parts of 325 mesh silicon carbide, 12 parts of 200 mesh silicon nitride iron, 6 parts of 200 mesh Guangxi mud, 12 parts of 200 mesh brown corundum, 3 parts of 325 mesh alumina powder, 0.3-0.5 parts of alkali-free glass fiber, 3 parts of zircon, 1-3 parts of 325 mesh carbon material, and 1 part of metallic silicon.
[0011] Preferably, the anti-leakage anhydrous taphole mud for the blast furnace taphole is made of the following components in parts by weight: 12 parts of homogenized alumina with a particle size of 1-3 mm, 12 parts of homogenized alumina with a particle size less than 1 mm, 11 parts of kyanite with a particle size not greater than 1 mm, 11 parts of silicon carbide with a particle size of 1-3 mm, 15 parts of 325 mesh silicon carbide, 12 parts of 200 mesh silicon nitride iron, 6 parts of 200 mesh Guangxi mud, 12 parts of 200 mesh brown corundum, 3 parts of 325 mesh alumina powder, 0.3 parts of alkali-free glass fiber, 3 parts of zircon, 1-3 parts of 325 mesh carbon material, and 1 part of metallic silicon.
[0012] Preferably, the anti-leakage anhydrous taphole mud for the blast furnace taphole is made of the following components in parts by weight: 12 parts of homogenized alumina with a particle size of 1-3 mm, 12 parts of homogenized alumina with a particle size less than 1 mm, 11 parts of kyanite with a particle size not greater than 1 mm, 11 parts of silicon carbide with a particle size of 1-3 mm, 15 parts of 325 mesh silicon carbide, 12 parts of 200 mesh silicon nitride iron, 6 parts of 200 mesh Guangxi mud, 12 parts of 200 mesh brown corundum, 3 parts of 325 mesh alumina powder, 0.3 parts of alkali-free glass fiber, 3 parts of zircon, 3 parts of medium-temperature expanded graphite, and 1 part of metallic silicon.
[0013] Preferably, the alkali-free glass fiber has an aspect ratio of 10 to 20:1, and a high-temperature liquid phase transition temperature of ≥1400°C.
[0014] Preferably, the medium-temperature expanded graphite has a fixed carbon content of ≥98%, an ash content of ≤10%, a S content of ≤1%, a moisture content of ≤1%, and an expansion temperature of 1000°C.
[0015] Preferably, the homogenized alumina contains Al2O3≥80%, Fe2O3≤1.6%, and TiO2≤4%.
[0016] A method for preparing the waterless taphole mud for preventing leakage at a blast furnace taphole comprises the following steps:
[0017] (1) After mixing the ingredients according to the proportion, add the aggregate into the mixer and grind for 5 minutes, and add 1 / 3 of the tar;
[0018] (2) premixing the powder in a premixing tank for 30 minutes to obtain a uniformly mixed premixed powder;
[0019] (3) The premixed powder is put into a mixer and mixed with aggregate for 5 minutes, and then 1 / 3 of tar is added. The mixing and grinding is continued for 30 minutes, and finally the remaining 1 / 3 of tar is added. The material is mixed and ground for 10 minutes and then discharged. The material is extruded, cut into blocks, and plastic-sealed to obtain anti-leakage anhydrous taphole mud for blast furnace taphole.
[0020] Preferably, the total amount of tar added is 10-11% of the total weight of the raw materials, and the Maxwell value is controlled to be 1300 kPa.
[0021] The method for preparing the waterless taphole mud for preventing leakage at the blast furnace taphole has a discharge temperature of 60-70°C.
[0022] Compared with other forms of graphite, medium-temperature expanded graphite has extremely high specific surface area and unit mass, which significantly enhances the toughness and thermal shock resistance of the material; its unique porous worm-like structure can produce deformation and recovery under external load and thermal shock conditions, showing excellent compressibility and resilience, and can absorb and release thermal stress in the system, thereby improving the thermal shock stability and toughness of refractory materials and improving the overall stability of the material; medium-temperature expanded graphite reacts with raw materials such as metallic silicon at high temperatures to promote the formation of a three-dimensional carbon network structure. During the material fracture process, this network structure helps the deflection, bridging, branching and pulling out of cracks, thereby producing a significant energy dissipation effect. Ultimately, these mechanisms can change the failure mode of the material, causing it to fail in the form of intercrystalline fracture, significantly improving fracture toughness, compressive strength, flexural strength and tensile strength.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] (1) The present invention adds alkali-free glass fiber, which significantly improves the flexural strength and toughness of the taphole mud through the interface bridging structure and energy dissipation mechanism, and reduces the risk of leakage. In addition, the high-temperature phase formed at high temperature enhances the sintering and high-temperature performance, reduces cracks and liquid slag iron intrusion, and further optimizes the performance of the taphole mud, which not only improves the overall flexural strength of the taphole mud, but also greatly reduces the risk of leakage at the junction of the taphole mud and the blast furnace wall;
[0025] (2) The present invention uses medium-temperature expanded graphite as a carbon source, which greatly improves the easy leakage-breaking property of the taphole mud. By utilizing the expansion characteristics of the medium-temperature expanded graphite, the shrinkage reaction of the taphole mud at high temperature is improved, the density of the taphole mud is increased, the cracking caused by the taphole mud line shrinkage is reduced, and the volume density of the taphole mud is increased;
[0026] (3) The present invention significantly improves the uniformity of the cannon mud by adding homogenized alumina; due to its dense structural characteristics, homogenized alumina effectively reduces the cannon mud's demand for oil adsorption, thereby reducing the amount of oil added to the cannon mud; this characteristic not only improves the plasticity of the cannon mud, but also enhances its compressive strength and overall stability. More importantly, the introduction of the dense structure of homogenized alumina optimizes the sintering performance of the cannon mud; under high-temperature use conditions, it can provide a stable skeleton structure, prevent the generation of cracks and improve erosion resistance;
[0027] (4) Compared with ordinary taphole mud, the anti-breakage anhydrous taphole mud prepared by the present invention has significant performance advantages; first, it can reduce the amount of mud on the basis of ensuring the depth of the taphole, optimize the operating efficiency of the taphole, help simplify the operating steps and save resources; second, the anti-breakage anhydrous taphole mud can significantly reduce the incidence of taphole leakage during the tapping process, thereby improving the safety and stability of blast furnace operation, which not only significantly reduces the blast furnace production upsets and economic losses caused by leakage, but also effectively protects the stability of blast furnace operation;
[0028] (5) The anti-leakage anhydrous taphole mud prepared by the present invention reduces the loss and consumption of the drill bit and the drill rod during the opening process, further reducing the production cost of the blast furnace. The application of this product in the operation of the blast furnace not only significantly improves the smelting efficiency, but also reduces the consumption of refractory materials in front of the furnace, prolongs the service life of the refractory materials, and has significant economic and technical value. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described below in conjunction with specific embodiments. In the following embodiments, unless otherwise specified, the technical means used are conventional means well known to those skilled in the art.
[0030] The alkali-free glass fiber used in the following examples has an aspect ratio of 10 to 20:1, a high-temperature liquid phase conversion temperature of ≥1400°C; the medium-temperature expanded graphite has a particle size of 325 mesh, fixed carbon ≥98%, ash ≤10%, S ≤1.0%, moisture ≤1.0%, and an expansion temperature of 1000°C; the homogenized alumina has Al2O3 ≥80%, Fe2O3 ≤1.60%, TiO2 ≤4.0% and a bulk density ≥3.4g / cm 3 .
[0031] Example 1
[0032] 1. A water-free taphole mud for preventing leakage at a blast furnace taphole, comprising the following components in parts by weight:
[0033]
[0034]
[0035] 2. Preparation method:
[0036] 1) Weigh the above solid powder according to the proportion, add the aggregate into the mixer, mix and grind for 5 minutes, and then add 1 / 3 of the tar binder;
[0037] 2) Premix the powder in a premixing tank for 30 minutes to ensure that the premixed powder is evenly mixed;
[0038] 3) Put the premixed powder mixed evenly in the premixing tank into the mixer and mix it with the aggregate for 5 minutes, then add 1 / 3 of tar;
[0039] 4) After continuing to mix and grind for 30 minutes, add the remaining 1 / 3 of tar, mix and grind for 10 minutes and then discharge the material. The discharge temperature is controlled at 60-70°C, and the material is extruded, cut into pieces, and plastic-sealed for packaging. The amount of tar binder added to the anhydrous taphole mud is controlled at 10-11%, and the Marshall value is controlled at 1300 kPa.
[0040] Example 2
[0041] A water-free taphole mud for preventing leakage at a blast furnace taphole, comprising the following components in parts by weight:
[0042]
[0043] The preparation method is the same as that in Example 1, and anhydrous taphole mud for preventing leakage at the blast furnace taphole is obtained.
[0044] Example 3
[0045] A water-free taphole mud for preventing leakage at a blast furnace taphole, comprising the following components in parts by weight:
[0046]
[0047] The preparation method is the same as that in Example 1, and anhydrous taphole mud for preventing leakage at the blast furnace taphole is obtained.
[0048] Example 4
[0049] 1. A water-free taphole mud for preventing leakage at a blast furnace taphole, comprising the following components in parts by weight:
[0050]
[0051]
[0052] 2. Preparation method:
[0053] The preparation method is the same as that in Example 1, and anhydrous taphole mud for preventing leakage at the blast furnace taphole is obtained.
[0054] Example 5
[0055] 1. A water-free taphole mud for preventing leakage at a blast furnace taphole, comprising the following components in parts by weight:
[0056]
[0057] The preparation method is the same as that in Example 1, and anhydrous taphole mud for preventing leakage at the blast furnace taphole is obtained.
[0058] Example 6
[0059] 1. A water-free taphole mud for preventing leakage at a blast furnace taphole, comprising the following components in parts by weight:
[0060]
[0061]
[0062] The preparation method is the same as that in Example 1, and anhydrous taphole mud for preventing leakage at the blast furnace taphole is obtained.
[0063] Example 7
[0064] 1. A water-free taphole mud for preventing leakage at a blast furnace taphole, comprising the following components in parts by weight:
[0065]
[0066]
[0067] The preparation method is the same as that in Example 1, and anhydrous taphole mud for preventing leakage at the blast furnace taphole is obtained.
[0068] Example 8
[0069] 1. A water-free taphole mud for preventing leakage at a blast furnace taphole, comprising the following components in parts by weight:
[0070]
[0071] The preparation method is the same as that in Example 1, and anhydrous taphole mud for preventing leakage at the blast furnace taphole is obtained.
[0072] Example 9
[0073] 1. A water-free taphole mud for preventing leakage at a blast furnace taphole, comprising the following components in parts by weight:
[0074]
[0075]
[0076] The preparation method is the same as that in Example 1, and anhydrous taphole mud for preventing leakage at the blast furnace taphole is obtained.
[0077] Comparative Example 1
[0078] 1. An anhydrous taphole mud, composed of the following components in parts by weight:
[0079]
[0080] The preparation method is the same as that in Example 1 to obtain anhydrous taphole mud.
[0081] Example 10
[0082] The performance of the anhydrous cannon clay prepared in Examples 1 to 9 and Comparative Example 1 was tested. A 40mm×40mm×160mm mold was prepared, the surface was cleaned and evenly coated with lubricating oil, the prepared anhydrous cannon clay was placed in the mold, and placed in the center of the pressure testing machine operating table to press with a pressure of 45kN, and the pressure was maintained for 30s; after demolding, it was placed at room temperature for 48 hours, heated to 1500℃, and stopped heating after 3h of charcoal heat treatment, and the sample was taken out after natural cooling to room temperature with the furnace, and the sample was tested, wherein: the volume density and apparent porosity of the cannon clay after calcination at 1500℃ were tested with reference to GB / T 2997-2000; the compressive strength and flexural strength of the cannon clay after calcination were tested with a microcomputer-controlled electro-hydraulic servo universal testing machine, and the linear change rate = (L 处理后 -L 初始 ) / L 初始 ×100% to calculate the linear change rate of taphole mud. The results are shown in Table 1.
[0083] Table 1 Performance indexes of anhydrous taphole mud prepared in Examples 1 to 9 and Comparative Example 1 after burning at 1500°C
[0084]
[0085] The anti-leakage anhydrous taphole clay prepared in Example 9 of the present invention was applied to a 5010 cubic meter blast furnace, and the results are shown in Table 2. Among them, the ordinary taphole clay was prepared in Comparative Example 1.
[0086]
[0087] It can be seen from Tables 1 and 2 that the anhydrous taphole mud prepared by the present invention has good performance, optimizes the taphole operation efficiency, reduces the risk of leakage, and significantly improves the safety and stability of blast furnace operation.
[0088] The high-temperature phase formed by the alkali-free glass fiber added in the present invention at high temperature enhances sintering and high-temperature performance, reduces cracks and liquid slag iron intrusion, and further optimizes the performance of cannon mud. Medium-temperature expanded graphite significantly enhances the toughness, thermal shock resistance and volume stability of cannon mud due to its porous structure and high specific surface area. Its carbon network structure formation mechanism at high temperature significantly improves fracture toughness and mechanical strength, while improving high-temperature density and linear shrinkage resistance, greatly reducing the possibility of cannon mud leakage. Homogenized alumina improves uniformity, plasticity and compressive strength in cannon mud due to its stable composition and high density, optimizes sintering performance, and under high temperature conditions, its stable skeleton structure enhances erosion resistance, reduces crack generation, and effectively improves the overall stability of cannon mud.
[0089] The present invention adopts an advanced automated production process for cannon clay, and ensures the accuracy and uniformity of the raw material components through full digital control and a precise batching system. At the same time, the temperature, time and mixing parameters in the production process are strictly monitored to ensure the density and strength of the cannon clay. The strict process not only improves production efficiency, but also greatly reduces quality fluctuations, thereby ensuring the high stability and consistency of the product, and providing reliable protection for blast furnace operations. Anti-leakage anhydrous cannon clay optimizes the iron mouth operation efficiency, reduces the risk of leakage, significantly improves the safety and stability of blast furnace operations, and reduces the consumption of drill bits and refractory materials, extending the material life. It has significant advantages in both technology and economy, bringing higher smelting efficiency and economic benefits to blast furnace operations.
[0090] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A waterless taphole mud for preventing leakage at a blast furnace taphole, characterized in that: Made from the following components in parts by weight: 8-16 parts of homogenized alumina with a particle size of 1-3mm, 8-16 parts of homogenized alumina with a particle size less than 1mm, 7-15 parts of kyanite with a particle size not greater than 1mm, 7-15 parts of silicon carbide with a particle size of 1-3mm, 10-20 parts of 325 mesh silicon carbide, 8-16 parts of 200 mesh silicon ferronitride, 4-8 parts of 200 mesh Guangxi mud, 8-16 parts of 200 mesh brown corundum, 2-4 parts of 325 mesh alumina micropowder, 0-0.5 parts of alkali-free glass fiber, 2-3 parts of zircon, 1-3 parts of carbon black or medium-temperature expanded graphite, and 1-2 parts of metallic silicon.
2. The water-free taphole mud for preventing leakage at the blast furnace tap hole according to claim 1, characterized in that: Made from the following components in parts by weight: 12 parts of homogenized alumina with a particle size of 1-3mm, 12 parts of homogenized alumina with a particle size less than 1mm, 11 parts of kyanite with a particle size not greater than 1mm, 11 parts of silicon carbide with a particle size of 1-3mm, 15 parts of 325 mesh silicon carbide, 12 parts of 200 mesh silicon ferronitride, 6 parts of 200 mesh Guangxi mud, 12 parts of 200 mesh brown corundum, 3 parts of 325 mesh alumina powder, 0.3-0.5 parts of alkali-free glass fiber, 3 parts of zircon, 1-3 parts of medium-temperature expanded graphite, and 1 part of metallic silicon.
3. The water-free taphole mud for preventing leakage at the blast furnace taphole according to claim 2, characterized in that: Made from the following components in parts by weight: 12 parts of homogenized alumina with a particle size of 1-3mm, 12 parts of homogenized alumina with a particle size less than 1mm, 11 parts of kyanite with a particle size not greater than 1mm, 11 parts of silicon carbide with a particle size of 1-3mm, 15 parts of 325 mesh silicon carbide, 12 parts of 200 mesh silicon ferronitride, 6 parts of 200 mesh Guangxi mud, 12 parts of 200 mesh brown corundum, 3 parts of 325 mesh alumina powder, 0.3 parts of alkali-free glass fiber, 3 parts of zircon, 1-3 parts of medium-temperature expanded graphite, and 1 part of metallic silicon.
4. The water-free taphole mud for preventing leakage at the blast furnace tap hole according to claim 3, characterized in that: Made from the following components in parts by weight: 12 parts of homogenized alumina with a particle size of 1-3mm, 12 parts of homogenized alumina with a particle size less than 1mm, 11 parts of kyanite with a particle size not greater than 1mm, 11 parts of silicon carbide with a particle size of 1-3mm, 15 parts of 325 mesh silicon carbide, 12 parts of 200 mesh silicon ferronitride, 6 parts of 200 mesh Guangxi mud, 12 parts of 200 mesh brown corundum, 3 parts of 325 mesh alumina powder, 0.3 parts of alkali-free glass fiber, 3 parts of zircon, 3 parts of medium-temperature expanded graphite, and 1 part of metallic silicon.
5. The water-free taphole mud for preventing leakage at the blast furnace tap hole according to claim 1, characterized in that: The alkali-free glass fiber has an aspect ratio of 10 to 20:1, and a high-temperature liquid phase conversion temperature of ≥1400°C.
6. The water-free taphole mud for preventing leakage at the blast furnace tap hole according to claim 4, characterized in that: The medium-temperature expanded graphite has a fixed carbon content of ≥98%, an ash content of ≤10%, an S content of ≤1%, a moisture content of ≤1%, and an expansion temperature of 1000°C.
7. The water-free taphole mud for preventing leakage at the blast furnace tap hole according to claim 1, characterized in that: The homogenized alumina contains Al2O3≥80%, Fe2O3≤1.6%, and TiO2≤4%.
8. A method for preparing the waterless taphole mud for preventing leakage at a blast furnace tap hole according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) After mixing the ingredients according to the proportion, add the aggregate into the mixer and grind for 5 minutes, and add 1 / 3 of the tar; (2) premixing the powder in a premixing tank for 30 minutes to obtain a uniformly mixed premixed powder; (3) The premixed powder is put into a mixer and mixed with aggregate for 5 minutes, and then 1 / 3 of tar is added. The mixing and grinding is continued for 30 minutes, and finally the remaining 1 / 3 of tar is added. The material is mixed and ground for 10 minutes and then discharged. The material is extruded, cut into blocks, and plastic-sealed to obtain anti-leakage anhydrous taphole mud for blast furnace taphole.
9. The method for preparing the waterless taphole mud for preventing leakage at the blast furnace tap hole according to claim 8, characterized in that: The total amount of tar added is 10-11% of the total weight of the raw materials, and the Marshall value is controlled to be 1300 kPa.
10. The method for preparing anhydrous taphole mud for preventing leakage at a blast furnace tap hole according to claim 8, characterized in that: The discharge temperature is 60-70°C.
Citation Information
Patent Citations
A high-strength anti-corrosion taphole mud and preparation method thereof
CN118005413B